The Impact of Orthodox Church Tradition as Authority on the Identity and Theology of Evangelical Christians in the Commonwealth of Independent States - Alexander LIKHOSHERSTOV (Богословські роздуми: Східноєвропейський журнал богословʼя)
The article examines both normative and practical significance of Orthodox Church Tradition Authority, as a theological category, for Evangelical Christians in Russia and CIS countries, who have still been looking for a distinct Christian identity in a predominant Orthodox background. The necessity of approaching the complicated issue of Scripture and Tradition relationship and its authority from the perspective of contemporary Evangelical theology does not include only a theological interest and practical implications, but also presumes (1 Peter 3:15) that all Christians, including Protestants, have always been called on to defend their integrity of faith, certain ly no less today than at any other time in history. The author suggests that contemporary Evangelical theology needs to facilitate the formation of a distinctive Evangelical approach toward the issue of authority of Orthodox Church Tradition for Evangelical Christians in both conceptual development (theological articulation of modern Protestant position) and practical apologetic implications of theological advancement in understanding historical, hermeneutical, Christological and theolog ical aspects of the issue.